1990
DOI: 10.1002/syn.890050306
|View full text |Cite
|
Sign up to set email alerts
|

Pargyline‐Sensitive selective accumulation of a radiolabeled MPTP analog in the primate cerebral cortex and basal ganglia

Abstract: The distribution of radioiodinated N-methyl-4-(4-hydroxy-3-iodobenzyl)-1,2,3,6-tetrahydropyridine (MHTP), an analog of the reportedly nontoxic N-methyl-4-benzyl-1,2,3,6-tetrahydropyridine, (4-homo-MPTP), has been studied in the primate. [123I]MHTP-derived radioactivity exhibited a progressive accumulation and prolonged retention within the primate eye. Following iv injection, [123I]MHTP rapidly accumulated within the primate brain and was subsequently oxidized to a radiolabeled metabolite. The half-life of [12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Radiolabelling studies demonstrated that the highest concentrations of radioactivity following the intravenous injection of a radiolabelled MPTP analogue were found in the caudate-putamen and the frontal, temporal and cingulate cortices; the substantia nigra and inferior olivary nucleus were labelled with medium intensity. Only very low concentrations of the radiolabelled analogue were detected in the cerebellum and white matter (12).…”
Section: Discussionmentioning
confidence: 93%
“…Radiolabelling studies demonstrated that the highest concentrations of radioactivity following the intravenous injection of a radiolabelled MPTP analogue were found in the caudate-putamen and the frontal, temporal and cingulate cortices; the substantia nigra and inferior olivary nucleus were labelled with medium intensity. Only very low concentrations of the radiolabelled analogue were detected in the cerebellum and white matter (12).…”
Section: Discussionmentioning
confidence: 93%
“…The syntheses of radiolabeled forms of N , N -dimethylphenylethylamine were reported, initial biodistribution studies were reported in rodents, and even a single human PET image was presented . Preliminary studies in both rat and primate were also done with carbon-11-labeled MPTP and a radioiodinated tetrahydropyridine ( N -methyl-4-(4′-hydroxy-3′-[ 125 I]­iodophenyl)-1,2,3,6-tetrahydropyridine), but no additional reports were made for use of either compound. Further development and validation (demonstration of isoform selectivity, pharmacokinetic analyses) of noncovalent metabolic trapping radiotracers for MAO have not been pursued, and there have been no applications of this concept to studies of MAO in human diseases.…”
mentioning
confidence: 99%